2004
DOI: 10.1210/jc.2003-031870
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in the Distribution ofRET/PTCRearrangements within Individual Post-Chernobyl Papillary Thyroid Carcinomas

Abstract: The nuclear disaster that occurred in Chernobyl in 1986 offered the unique opportunity to study the molecular genetics of one human tumor type, papillary carcinoma of the thyroid gland, associated with a specific etiology. We have analyzed RET rearrangements in post-Chernobyl papillary thyroid carcinomas (n = 29), follicular thyroid adenomas (n = 2), and follicular thyroid carcinoma (n = 1) by interphase fluorescence in situ hybridization (FISH) analysis on paraffin-embedded tissue sections. Paraffin sections … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
101
1
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(116 citation statements)
references
References 16 publications
9
101
1
5
Order By: Relevance
“…An interesting finding of this study is the deletion of RET because its activated form, RET/PTC, is known as a marker of PTC. This apparent contradiction, being simultaneously present as an activated oncogene and affected by a deletion, can be explained by a distinct genetic heterogeneity in tumour tissues as already extensively reported for RET/PTC (Unger et al, 2004Ciampi and Nikiforov, 2007). We confirmed this genetic heterogeneity for RET/PTC by performing RET/PTC analysis at a single-cell level by FISH in this study (data not shown).…”
Section: Array Cgh On Ptc K Unger Et Alsupporting
confidence: 86%
See 3 more Smart Citations
“…An interesting finding of this study is the deletion of RET because its activated form, RET/PTC, is known as a marker of PTC. This apparent contradiction, being simultaneously present as an activated oncogene and affected by a deletion, can be explained by a distinct genetic heterogeneity in tumour tissues as already extensively reported for RET/PTC (Unger et al, 2004Ciampi and Nikiforov, 2007). We confirmed this genetic heterogeneity for RET/PTC by performing RET/PTC analysis at a single-cell level by FISH in this study (data not shown).…”
Section: Array Cgh On Ptc K Unger Et Alsupporting
confidence: 86%
“…However, the identification of RET/PTC in other common thyroid tumour histotypes such as oncocytic adenomas and carcinomas (Cheung et al, 2000), and even in hyperplastic thyroid nodules (Ishizaka et al, 1991;Elisei et al, 2001) and Hashimoto's thyroiditis (Rhoden et al, 2006), seems to challenge the validity of RET/PTC as a tumour marker and its specificity for PTC. Moreover, it has been recently shown that the level of RET/PTC expression in papillary carcinoma is highly variable, suggesting that the distribution of RET/PTC within one tumour may not be homogenous (Rhoden et al, 2004;Unger et al, 2004). This is also supported by recent fluorescence in situ hybridization (FISH) studies by ourselves and others (Unger et al, 2004;Ciampi and Nikiforov, 2007).…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…53,54 Using fluorescence in situ hybridization (FISH), Unger et al 53 revealed that within a single PTC, only a subset of tumour cells (not more than 46%) showed RET/PTC rearrangement beside areas completely lacking tumour cells with RET/PTC rearrangement. In contrast to these studies, Zhu et al 54 using FISH technique reported that the vast majority (50-86%) if not all tumour cells carried the rearrangement.…”
Section: Discussionmentioning
confidence: 99%